Wearable smartphone sync wireless remote health monitoring system - Abd Razak, Nurul Nabilah; Sidek, Khairul Azami (Malaysia Technical Scientist Association, 2018)
Photoplethysmogram (PPG) signal is found to have potentials to detect pulse rate, Galvanic Skin Response (GSR) signal to detect skin conductivity and skin temperature as in real time data as well as history data through Bluetooth wireless commu-nication. All the signals utilized in this paper are obtained from few experiments done, which contains of various PPG and GSR signals from volunteers. The features of PPG and GSR signals such as the beginning and end point of a cycle of PPG signal and its peaks then will be extracted using Processing.org. Test results from a group of volunteers shows the real-time temperature reading successfully monitored locally (at home). The reading taken are the pulse rate, body temperature and skin conductivity. Based on the experimentation result, it can be observed that female have higher pulse rate as compared to male. Besides that, for body temperature, male have higher body temperature than female. For skin conductivity, male have higher skin conductivity than female due to their physical activity. The readings had been later compared to commercial pulse rate, body temperature thermometer as well as skin conductivity device. Based on the benchmarking, all three sensors has error which is less than 3% which shows that it is good reliable. In addition, this study is a better alternative to the cur-rent approaches since it combines three test parameters in one portable device. Thus the research will propose a remote health monitoring system which combines three vital tests parameters to facilitate caretakers, medical practitioners in observ-ing the patient in need.